Tillage and precision nutrient placement effects on soil microbial dynamics and nutrient uptake of maize - Prakash Sonnad; Teekam Singh; Ramanjit Kaur; Raj Singh; Tanmay Das; Huchchappa Jamakhandi (Annals of Agricultural Research, 2025)
Field study was carried out during rainy (kharif) season of 2022-23 at Research Farm, Division of Agronomy, ICAR-IARI, New Delhi. The experiment was laid out in a split-plot design with 3-tillage practices viz., T1 (conventional tillage); T2 (once rotavator as minimum tillage) and T3 (zero tillage) in main plots and 4-precise nutrients application options viz., N1-50% RDF as point placement; N2-75% RDF as band placement; N3- 100% RDF as band placement and N4-100% RDF as broadcasting and replicated thrice. Results revealed that zero tillage (T3) has resulted 41% MBC, 44.53% dehydrogenase activity and 19.2% higher FDA activity in the soil compared to conventional tillage (T1) which is mainly due to crop residue cover in ZT. The maximum total N, P and K uptake as well as the protein content (11.20%) in maize grain were recorded with minimum tillage, while the minimum uptake of all these nutrients and protein content were recorded with conventional tillage. The maximum partial factor productivity of N, P and K were recorded with minimum tillage compared to conventional tillage. The 100% RDF through band placement (N3) resulted 11.6% MBC, 21.6% dehydrogenase activity and 13.23% higher FDA activity in the soil compared to 100% RDF as broadcasting. The maximum N, P and K uptake and protein content in maize grains were recorded with 100% RDF of band placement, however, remained statistically at par with 50% RDF of point placement. The findings suggested that zero tillage enhance soil health but minimum tillage and precise nutrient point placement could significantly enhance nutrient uptake and partial factor productivity in kharif season of maize, offering 50% reduction in fertilizer consumption.